2016
DOI: 10.1016/j.jccase.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Intra-cardiac thrombus in antiphospholipid antibody syndrome: An unusual cause of fever of unknown origin with review of literature

Abstract: Antiphospholipid antibody syndrome (APS) commonly presents with thrombotic events, pregnancy morbidity, and recurrent pregnancy loss [1]. APS presenting as fever of unknown origin (FUO) is rare. To date, there are only a few case reports that have described FUO as presenting manifestation of APS [2]. Intra-cardiac thrombus and pulmonary thromboembolism (PTE) are lifethreatening thrombotic events of APS, but asymptomatic presentation of intra-cardiac thrombus with PTE is rare [3]. Case reportA 41-year-old man p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
(11 reference statements)
0
9
0
1
Order By: Relevance
“…Antiphospholipid syndrome (APLS) is a heterogeneous autoimmune disorder of hyper coagulation. It is manifested mostly as arterial and venous thrombosis, recurrent fetal loss and thrombocytopenia [ 1 ] and by presence of antiphospholipid antibodies (aPL) such as anticardiolipin antibodies and lupus anticoagulant [ 2 ]. Antiphospholipid syndrome has varying presentations and can manifest in any organ system thus requiring multidisciplinary team for optimal management.…”
Section: Introductionmentioning
confidence: 99%
“…Antiphospholipid syndrome (APLS) is a heterogeneous autoimmune disorder of hyper coagulation. It is manifested mostly as arterial and venous thrombosis, recurrent fetal loss and thrombocytopenia [ 1 ] and by presence of antiphospholipid antibodies (aPL) such as anticardiolipin antibodies and lupus anticoagulant [ 2 ]. Antiphospholipid syndrome has varying presentations and can manifest in any organ system thus requiring multidisciplinary team for optimal management.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, our patient had a right atrial thrombosis that was associated with secondary APS, which has a higher risk of thrombosis and valvular disease than patients who do not have antiphospholipid antibodies [ 15 ]. In addition, others [ 10 , 16 , 17 ] have pointed out that when the thrombus in the cardiac cavity is large and irregular, it easly falls off and leads to a very high risk of recurrent pulmonary embolism. In this patients, pulmonary CT showed inflammation and consolidation changes in both lungs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Although intracardiac thrombus is rare, it is reported to be most common in the right atrium and is more frequently associated with P-APLS as compared to S-APLS. [ 6 ] Although there are no data specific to LV thrombus, available literature suggests that the presence of high levels of LA and aCL was significantly associated with arterial[ 7 ] and intracardiac thrombosis. [ 8 ] A 5-year prospective study also showed that the median time to a recurrent thrombotic event is shorter in patients with high titer of aCL antibody and intracardiac thrombus.…”
Section: Discussion and M Ini-review Of The L Iteraturementioning
confidence: 99%